Pulmonary blood flow distribution after banding of pulmonary artery. Issue 1 (January 1975) - Samánek, M; Fiser, B; Ruth, C; Tůma, S; Hucín, B
Abstract : Radioisotope lung scanning was used to investigate the distribution of pulmonary blood flow after banding of the pulmonary artery in children with a left-to-right shunt and pulmonary hypertension. An abnormal distribution of blood flow in the lung on the side of the operation approach was observed in all patients in the first three weeks following surgery. Abnormalities were still observed in 17 of 21 children 10 months to more than 8 years after the banding operation. There was no significant relation between the occurrence of these abnormalities and time after surgery. Diminished flow to the zones of the right lung was observed less frequently. The incidence of abnormalities in flow distribution was also high preoperatively. Respiratory complications in infants with large left-to-right shunts were considered to be responsible for most of the abnormal blood flow distributions observed. Radioactive lung scanning was found to be a valuable diagnostic method in the early and late postoperative period in infants and small children. It was more sensitive than the other techniques used in revealing deviation of blood flow from one lung in those cases with shifting of the applied band.